Maternity Leave Under the FMLA: An Analysis of the Litigation Experience - Rafael Gely; Timothy D. Chandler (Washington University Journal of Law & Policy, 2004)
We begin with a brief description of trends in female labor force participation and the presence of dual-earner households in the U.S. labor market, conditions which likely led to the need for family and medical leave legislation. We then review various practices that business and government organizations have implemented to balance work and family conflicts, as well as related features of the FMLA, particularly those pertaining to childbirth and adoption. With this background in place, we introduce a framework for examining FMLA litigation. We then review cases litigated in federal court under the FMLA involving requests for family leave due to the birth or adoption of a child to determine the nature of conflicts occurring under the legislation and the resolution of those conflicts by the courts.
Keywords: Parental leave; Family and Medical Leave Act of 1993